Major channels involved in neuropsychiatric disorders and therapeutic perspectives - Imbrici, Paola; Conte Camerino, Diana; Tricarico, Domenico (Frontiers in Genetics, 2013)
Voltage-gated ion channels are important mediators of physiological functions in the central nervous system. The cyclic activation of these channels influences neurotransmitter release, neuron excitability, gene transcription and plasticity, providing distinct brain areas with unique physiological and pharmacological response. A growing body of data has implicated ion channels in the susceptibility or pathogenesis of psychiatric diseases. Indeed, population studies support the association of polymorphisms in calcium and potassium channels with the genetic risk for bipolar disorders or schizophrenia. Moreover, point mutations in calcium, sodium and potassium channel genes have been identified in some childhood developmental disorders. Finally, antibodies against potassium channel complexes occur in a series of autoimmune psychiatric diseases. Here we report recent studies assessing the role of calcium, sodium and potassium channels in bipolar disorder, schizophrenia and autism spectrum disorders, and briefly summarize promising pharmacological strategies targeted on ion channels for the therapy of mental illness and related genetic tests.